2008
DOI: 10.1021/jp8000866
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetrics Studies of the Thermodynamics and Binding Mechanism between l-Tyrosinamide and Aptamer

Abstract: In recent years, several high-resolution structures of aptamer complexes have shed light on the binding mode and recognition principles of aptamer complex interactions. In some cases, however, the aptamer complex binding behavior and mechanism are not clearly understood, especially with the absence of structural information. In this study, it was demonstrated that isothermal titration calorimetry (ITC) and circular dichroism (CD) were useful tools for studying the fundamental binding mechanism between a DNA ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
64
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 71 publications
13
64
1
Order By: Relevance
“…Since the same concentrations of HApt were analyzed for free HApt and HApt-MNPs, the larger peak values for HApt-MNPs may be caused by condensation of HApt within the MNPs. [46][47][48] The CD spectra of the free and MNP-encapsulated NCApt were similar ( Figure S1). …”
Section: Mnp-encapsulated Hapt Is Structurally Similar To Free Haptmentioning
confidence: 87%
“…Since the same concentrations of HApt were analyzed for free HApt and HApt-MNPs, the larger peak values for HApt-MNPs may be caused by condensation of HApt within the MNPs. [46][47][48] The CD spectra of the free and MNP-encapsulated NCApt were similar ( Figure S1). …”
Section: Mnp-encapsulated Hapt Is Structurally Similar To Free Haptmentioning
confidence: 87%
“…ÁH values as high as -150 kJ/mol can be retrieved, even for a small target binding to aptamer [31,32]. Such very favourable enthalpic contribution can be attributed not only to the formation of strong intermolecular bonds between the target and the aptamer (see above), but also to the target-induced intramolecular interactions within the aptamer.…”
Section: Molecular Recognition Properties Of the Nucleic Acid Aptamersmentioning
confidence: 97%
“…Such argininamide encapsulation would be accompanied by a strong reduction of the solvent accessible surface area upon complex formation, in the order of 1000 2 [31]. Another circular dichroism analysis has shown that the anti-tyrosinamide DNA aptamer undergoes a DNA B-form to A-form transition upon the target binding [32]. For a larger target such as proteins, both the aptamer and the target are assumed to display conformational adaptability allowing the association between the two partners [21].…”
Section: Molecular Recognition Properties Of the Nucleic Acid Aptamersmentioning
confidence: 99%
“…30,31 In order to have a better insight into the interaction between S-5-1 and systemin, the influences of pH and ionic strength on aptamer binding were evaluated. Usually, hydrogen bonds, electrostatic interactions, stacking interactions, molecular shape complementarity and hydrophobic effect are considered to be involved in the binding between an aptamer and its target molecule.…”
Section: The Effect Of Ionic Strength and Ph On Aptamer Bindingmentioning
confidence: 99%